Lactate-Induced H3K18 Lactylation Attenuates T-Cell Activation and Upregulates PD-L1 in Esophageal Squamous Cell Carcinoma - Tao Liu; Guanghong He; Wenshou Zhong; Xiaoming Lin; Rong Liang; Xianjin Huang (Discovery Medicine, 2026)
Background: Immune checkpoint blockade targeting the Programmed Death-1 (PD-1)/Programmed Death-Ligand 1 (PD-L1) axis has demonstrated clinical activity in esophageal squamous cell carcinoma (ESCC). However, therapeutic responses remain limited in a substantial proportion of patients. Metabolic reprogramming and lactate accumulation are hallmarks of the tumor microenvironment and have been implicated in immune suppression, yet the epigenetic mechanisms linking lactate metabolism to immune checkpoint regulation in ESCC remain poorly understood. The aim of this study was to investigate whether lactate-induced histone lactylation regulates PD-L1 expression and contributes to tumor-intrinsic PD-L1 regulation in ESCC.Methods: ESCC cell lines were treated with exogenous lactate and metabolic modulators to evaluate PD-L1 expression and histone H3 lysine 18 lactylation (H3K18la). The involvement of the lactyltransferase p300 was assessed using pharmacological inhibition. T cell function was examined using an in vitro co-culture system with activated Jurkat T cells. In vivo validation was performed using a nude mouse xenograft model, followed by immunohistochemical analysis.Results: Lactate treatment significantly increased PD-L1 expression in ESCC cells (p < 0.001), accompanied by elevated global H3K18la (p < 0.001). Inhibition of glycolysis reduced basal H3K18la and PD-L1 expression (p < 0.001), which was restored by exogenous lactate (p < 0.001). Pharmacological inhibition of p300 abrogated lactate-induced H3K18la and PD-L1 upregulation (p < 0.001), indicating a p300-dependent mechanism. Functionally, lactate-treated ESCC cells reduced the expression of the activation-associated cytokines Interleukin-2 (IL-2) and Interferon-gamma (IFN-γ) in co-cultured Jurkat T cells (p < 0.001), indicative of attenuated T-cell activation, an effect partially reversed by PD-L1 knockdown. In vivo, lactate administration increased intratumoral H3K18la and PD-L1 expression in xenograft tumors (p < 0.001).Conclusions: Our findings identify a lactate-p300-H3K18 lactylation axis associated with transcriptional upregulation of PD-L1 and attenuation of T-cell activation in a Jurkat-based co-culture system, providing a metabolic-epigenetic framework for improving immunotherapeutic strategies.